Products exchange in a multi-level multi-period distribution network with limited storage capacity - Benfriha, Abdennour -Ilyas; Triqui-Sari, Lamia; Bougloula, Aimed-Eddine; BENNEKROUF, Mohammed (2nd International Conference on Innovative Research in Applied Science, Engineering and Technology (IRASET), 2022)
Cooperation in distribution network has attracted the interest of researchers. In this study we analyse an inventory problem in distribution network, where we propose a cooperative platform that allow the members of the network to share and use local inventory of other members to meet their local demand. We develop a MIP models representing the traditional network and the network with the cooperative platform. Then we solve it using LINGO solver. We found that the proposed approach has reduced the total cost of the network and reduce the overstock and stock-out situation, which lead to improve the quality of service.